A community engaged exploratory study investigating the risk of elder abuse and neglect in two refugee communities in Greensboro, North Carolina. Issue 4 (8th August 2022) - Shreeniwas, Sudha; Khadka, Narayan
ABSTRACT: Elder abuse and neglect (EAN) are serious health and human rights issues. Less is known about EAN in refugee communities. University researchers and leaders of a refugee services nonprofit partnered to conduct an exploratory community engaged study on EAN risks in two refugee communities in North Carolina. A convenience sample of 17 Nepali-speaking Bhutanese and 13 Congolese self-identified older adults filled short surveys and participated in Focus Group Discussions (FGDs). Descriptive survey findings showed EAN risk, isolation, economic insecurity, and family dependency, more among Congolese. FGDs yielded no reports of EAN, but showed dependence on family, and difficulties with language, transportation, and economic insecurity in both groups. These factors indicate individual and contextual vulnerabilities for EAN in these communities. An EAN awareness event was conducted for participants by a family violence nonprofit. Refugee older adults need culturally appropriate coordinated services including EAN information, English classes, job skills, income, and transportation.